Efficiency and productivity differential effects of land certification program in Ethiopia: Quasi-experimental evidence from Tigray - Ghebru, Hosaena; Holden, Stein (International Food Policy Research Institute, 2014)
Taking advantage of a unique quasi-experi-mental survey design, this study analyzes the productivity impacts of the Ethiopian land certification program by identify-ing how the investment effects (technological gains) would measure up against the benefits from any improvements in input use intensity (technical efficiency). For this purpose, we adopted a data envelopment analysis-based Malmquist-type productivity index to decompose productivity differences into (1) within-group farm efficiency differences, reflecting the technical efficiency effect, and (2) differences in the group production frontier, reflecting the long-term investment (technological) effects. The results show that farms without a land use certificate are, on aggregate, less productive than those with formalized use rights.